PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA KOTAK BERHITUNG (KOBER) TERHADAP HASIL BELAJAR SISWA KELAS II SDI LABUANG PAKANGKANG NO.79 KEPULAUAN SELAYAR - Triulianti, Andi; Syam, Herul; Firdaus, Andi Mulawakkan (Sindoro: Cendikia Pendidikan, 2024)
The main problem in this research is the lack of numeracy skills students towards mathematics subjects, especially addition and subtraction. This research aims to determine the effectiveness in improving students' numeracy skills, activities in mathematics learning activities using the STAD type cooperative learning model assisted by counting box media (kober) in class II students at SDI Labuang Pakangkang No.79, Selayar Islands.This type of research is pre-experimental research. The research design is a Pretest-Posttest Design, namely an experiment whose implementation only involves one class as an experimental class without a comparison class (control class). The subjects used in this research were class II, totaling 20 students. Research instrument What was used was a pretest, posttest, and observation sheet. The data analysis techniques used were descriptive statistical data analysis techniques and inferential data analysis.Based on the results of descriptive statistical analysis of the application of the STAD type cooperative learning model assisted by counting box media (kober) on students' numeracy skills, students' Mathematics learning outcomes with the application of the STAD type cooperative learning model assisted by counting box media (kober) show better learning outcomes than before implementing the STAD type cooperative learning model assisted by counting box media (kober)The results of inferential statistical analysis using the t-test formula, it is known that the value of ????????i????????????&=9.92 while the value of ???????????????????????? = 1.729 at the significance level ???? = 0.05. Based on this value, it is obtained that ????????i????????????& > ????????????????????????, this means that H0 is rejected and then H1 is accepted. The results of the analysis of student activity data resulted in a score of 86%, which indicates the active category. So it can be concluded that the application of the STAD type cooperative learning model assisted by counting box media (kober) in mathematics for class II students at SDI Labuang Pakangkang No.79 Selayar Islands is said to be effective.